Regulation and Function of Proline Oxidase under Nutrient Stress - Pandhare, Jui (2009)
Under conditions of nutrient stress, cells switch to a survival mode catabolizing cellular and tissue constituents for energy. Proline metabolism is especially important in nutrient stress because proline is readily available from the breakdown of extracellular matrix (ECM), and the degradation of proline through the proline cycle initiated by proline oxidase (POX), a mitochondrial inner membrane enzyme, can generate ATP. This degradative pathway generates glutamate and α-ketoglutarate, products that can play an anaplerotic role for the TCA cycle. In addition the proline cycle is in a metabolic interlock with the pentose phosphate pathway providing another bioenergetic mechanism. Herein we have investigated the role of proline metabolism in conditions of nutrient stress in the RKO colorectal cancer cell line. The induction of stress either by glucose withdrawal or by treatment with rapamycin, stimulated degradation of proline and increased POX catalytic activity. Under these conditions POX was responsible, at least in part, for maintenance of ATP levels. Activation of AMP-activated protein kinase (AMPK), the cellular energy sensor, by 5-aminoimidazole-4-carboxamide ribonucleoside (AICAR), also markedly upregulated POX and increased POX-dependent ATP levels, further supporting its role during stress. Glucose deprivation increased intracellular proline levels, and expression of POX activated the pentose phosphate pathway. Together, these results suggest that the induction of proline cycle under conditions of nutrient stress may be a mechanism by which cells switch to a catabolic mode for maintaining cellular energy levels.